Buddhist Complex of Nimogram Swat, Pakistan: Its History, Classification, Analysis and Chronology - Sardar, Badshah (Ancient Pakistan, 2016)
This research paper is focused on a very rare and important collection of large scale artefacts (467 stone images, 43 stucco pieces, 05 copper coins and 02 relic caskets) excavated from the site of Nimogram Swat. Single figures of Buddha, Bodhisattvas, narrative reliefs, decorative and architectural elements, and containers for relics associated with Gandhara religious architecture are all well represented in the collection. The antiquities discovered from the salvage excavations of Nimogram Buddhist complex were neither studied scientifically nor documented properly. Only one preliminary report published by the Department of Archaeology & Museums Government of Pakistan in 1968, no precise study has so for been conducted. Despite the artistic beauty of these sculptures and the high reputation of the site in the Gandhara region, except for a preliminary report no information is available for general public or scholars. As such, bulks of artefacts are damped and out of approach of any research. To trace the history of the collection, classify it based on style, analyse it for the subject matter, kind of material and workout its chronology by correlating it to the already established sequence of the Swat valley sites i.e. Butkara-I (Faccenna 1980-81), Saidu Sharif Stupa (Callieri 1989), Butkara III (Rahman 1990 & 1991), Shnaisha Gumbat (Rahman 1993) and Panr Stupa (Faccenna, Nizar Khan & Nadiem 1993). The main object of this paper is to examine directly the Nimogram collection (published & unpublished) and to evaluate its religious, cultural, historical and iconographical importance so far ignored. To know the nature and degree of foreign influences on the collection, a comprehensive comparative study and analysis is under process and a monograph will be published soon. This paper discuss selective stone art pieces of the collection, reveals different subjects i.e., narrative reliefs, the Buddha’s life events, miracles of Buddha, Buddha & Bodhisattva images and miscellaneous section covers architectural, decorative elements, reliquaries and relic caskets.